2023
DOI: 10.1111/1346-8138.16839
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autoimmune and inflammatory diseases and mental health conditions among an alopecia areata cohort from a US administrative claims database

Abstract: Alopecia areata (AA) is associated with an increased burden of autoimmune and inflammatory disease and mental health conditions that may have a negative impact on quality of life. However, the exact burden of comorbidities on US patients with AA and the clinical subtypes alopecia totalis (AT) and alopecia universalis (AU) compared with those without AA is not well understood. This retrospective cohort study aimed to assess the incidence rates and prevalence of AA and its clinical subtypes and examine the autoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…This is consistent with the findings from two recent systematic reviews and meta-analyses, and several large studies conducted in the USA, Europe, and Japan [ 11 , 18 , 22 ]. In the most recent systematic review and meta-analysis that included 102 studies, patients with AA had higher odds of having atopic dermatitis, allergic rhinitis, asthma, and unspecified atopic conditions [ 13 ]. In the same study, AA was positively associated with the risk of presenting several thyroid diseases and notably those with an autoimmune origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the findings from two recent systematic reviews and meta-analyses, and several large studies conducted in the USA, Europe, and Japan [ 11 , 18 , 22 ]. In the most recent systematic review and meta-analysis that included 102 studies, patients with AA had higher odds of having atopic dermatitis, allergic rhinitis, asthma, and unspecified atopic conditions [ 13 ]. In the same study, AA was positively associated with the risk of presenting several thyroid diseases and notably those with an autoimmune origin.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with controls without AA, these studies have shown that AA is associated with an increased prevalence of various comorbid conditions, especially atopic, autoimmune, and psychiatric disorders. A recent analysis of a national administrative claims database in the USA also observed higher rates for several autoimmune, inflammatory, and mental health conditions in patients with AA compared to a matched cohort of subjects without AA [ 13 ]. Similar findings were reported in two large studies conducted in Denmark and the UK [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The condition can be debilitating and it is associated with increased anxiety and depression noted among AA patients. 3 A survey study with over 500 participants reported poorer quality of life, negative psychological influence, and emotional burden due to AA. 4 Unfortunately, the etiology of AA is still not well known.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of AA is also highly variable with some reporting isolated patches of hair loss that resolve within months to other individuals experiencing chronic recalcitrant alopecia 2 . The condition can be debilitating and it is associated with increased anxiety and depression noted among AA patients 3 . A survey study with over 500 participants reported poorer quality of life, negative psychological influence, and emotional burden due to AA 4 …”
Section: Introductionmentioning
confidence: 99%